PTU-256 New pelvic radiotherapy techniques do not eliminate gastrointestinal toxicity. (22nd June 2015) - White, KL; Routledge, J; Livsey, JE; Lisa, BH; Mclaughlin, J; Davidson, SE
Abstract : Introduction: Volumetric Modulated Arc Therapy (VMAT) is a recent technique of external beam radiotherapy. VMAT delivers less radiation dose to the bowel than traditional conformal therapy. This should lessen gastrointestinal (GI) acute toxicity however this has not yet been shown. We aimed to determine the rate of GI toxicity in the treatment of gynaecological malignancy with VMAT. Method: This prospective study included patients commencing radiotherapy from December 2013 to July 2014. Patients completed questionnaires prior to commencing radiotherapy, on their final day of treatment (end of week 4) and at 8 weeks (median 57 days) following the end of treatment. The questionnaire used was a validated patient reported questionnaire derived from the CTCAE (Common Terminology Criteria for Adverse Events) grading system. Results: See Table 1 for patient demographics. All patients had 20 fractions of radiotherapy over 4 weeks with the exception of 1 patient who only completed 17 fractions. Of the 62 eligible patients 57 completed baseline questionnaires, 60 at end of treatment and 50 completed them 8 weeks later. At baseline 32% of patients reported diarrhoea, this rose to 75% at end of treatment and fell to 33% 8 weeks later. In line with this 11% of patients reported taking anti-diarrhoeal medication at baseline, 73% at end of treatment and 14% at the 3 rd time point. Forty percent of patients had grade 3–4 faecal urgency at baseline, 70% at end of treatment and 53% at the 3 rd time point. Grade 3–4 tenesmus was present in 15% at baseline, 27% at end of treatment and 8% 8 weeks later. No patients reported faecal incontinence at baseline. Faecal incontinence of any grade was reported by 29% at end of treatment and by 12% at the 3 rd time point. Patients reported whether difficulty controlling their bowels affected their daily activities. At baseline 2% reported that this was the case compared with 30% at end of treatment and 10% 8 weeks later. Rectal bleeding was reported by 5% at baseline and by 8% at end of treatment and at the 3 rd time point. Conclusion: Our data suggest that VMAT does cause acute GI toxicity during radiotherapy treatment although at early follow up much of this has improved. Future work is planned to demonstrate whether VMAT confers benefit over conformal treatment in terms of GI late effects. Disclosure of interest: None Declared.